2019
DOI: 10.1021/acs.est.8b06657
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Sulfamethoxazole by the Model Plant Arabidopsis thaliana

Abstract: Phytometabolism of antibiotics is a potentially significant route of human exposure to trace concentrations of antibiotics, prompting concerns about antibiotic resistance. The present study evaluated the metabolism of sulfamethoxazole (SMX), a commonly used sulfonamide antibiotic, by Arabidopsis thaliana. SMX was intensively metabolized by A. thaliana, with only 1.1% of SMX in plant tissues present as the parent compound after 10 days of exposure. Untargeted screening of extractable metabolites revealed that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 60 publications
2
69
0
Order By: Relevance
“…enzymatic oxidation of SMX by laccase for 24 h yielded 4 transformation products, the typical transformation products of SAs were identified and are shown in Figs S2 C, D and E, and the characteristic transformation product of SMX shown in Fig.S2B, which is e in agreement with the results of other researchers(Majewsky et al 2015;Huynh and Reinhold 2019;Reis et al 2020). The proposed degradation pathway is in Fig.3.…”
supporting
confidence: 88%
“…enzymatic oxidation of SMX by laccase for 24 h yielded 4 transformation products, the typical transformation products of SAs were identified and are shown in Figs S2 C, D and E, and the characteristic transformation product of SMX shown in Fig.S2B, which is e in agreement with the results of other researchers(Majewsky et al 2015;Huynh and Reinhold 2019;Reis et al 2020). The proposed degradation pathway is in Fig.3.…”
supporting
confidence: 88%
“…Although further uptake studies of sulfonamides from the soil to plants are required to understand the absorption and accumulation of veterinary medicines and their derived metabolites in plants, some of these studies [43,60] have suggested that the phyto-metabolism of antibiotics is a potentially significant route of human exposure to trace concentrations of antibiotics, which has prompted concerns about the development of antibiotic resistance in humans [76].…”
Section: Discussionmentioning
confidence: 99%
“…In phase II, xenobiotics or their activated phase I metabolites undergo conjugation with endogenous plant compounds [14]. Conjugation of xenobiotics in plants may happen with various substituents, such as acetyl, methyl, and sulfate groups, glucuronic acid, cladinose, glucose, glutathione, glucopyranosyloxy and malonyl groups, pterin, methyl salicylate, leucyl, glutamic acid, and glutamine molecules, amongst others [15][16][17][18][19]. As a result, phase II might yield "endless" conjugation possibilities in plants as a detoxification mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, only a few studies on the metabolization of sulfonamides (i.e. sulfamethoxazole, sulfadiazine, and sulfamethazine) [15][16][17]30], clarithromycin [16], and ofloxacin [31] in plants have been reported. For example, clarithromycin follows four major metabolic pathways in lettuce, including cladinose hydrolysis, demethylation, methylation, and oxidation [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation